Composite current collector, secondary battery, and electric device

CN119318038APending Publication Date: 2025-01-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380043850.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-01-16
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The tabs in the traditional composite current collector need to be welded through a transfer welding process, which leads to increased manufacturing costs, reduced energy density, poor welding, and insufficient overcurrent capability.

Method used

Design a composite current collector that forms a tab area at the end of the metal layer and connects it through an adhesive layer to form a ladder-like structure to enhance the overcurrent capacity and conductivity of the tab, avoid the transfer welding process, and use adhesive The binder fills gaps to improve stability.

Benefits of technology

It improves the overcurrent capacity and conductivity of the tabs, reduces manufacturing costs, enhances the energy density and safety of the battery, and avoids poor welding problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318038A_ABST
    Figure CN119318038A_ABST
Patent Text Reader

Abstract

The invention relates to a composite current collector which comprises a first metal layer, a second metal layer and a first bonding layer, the first metal layer comprises a first main body region and a first tab region, the first tab region is located at the end part of the first metal layer, the second metal layer comprises a second main body region and a second tab region, the second tab region is located at the end part of the second metal layer, the first main body region and the second main body region are connected through a first bonding layer, the thickness of the first tab region is greater than that of the first main body region, and the first tab region extends towards the second tab region; the invention also relates to a corresponding secondary battery and an electric device. The composite current collector has good current passing capability, and can enable the battery to have relatively high energy density and relatively good safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Composite current collector, secondary battery and electrical device Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite current collector, a secondary battery, and an electrical device. Background Art

[0002] In recent years, the application of secondary batteries has become increasingly widespread. They are widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. As secondary batteries have achieved great development, higher requirements have been placed on the current capacity of the tabs, the energy density, and safety of the secondary batteries.

[0003] In traditional secondary battery composite current collectors, the tabs must be attached to the metal layer of the current collector through an additional transfer welding process. This process not only introduces additional manufacturing costs but also requires the use of additional metal foil, which reduces the battery's energy density. Transfer welding can also easily lead to poor welds, such as cold joints.

[0004] Therefore, seeking a composite current collector that can improve the flow capacity, has a higher energy density and better safety is one of the key areas of focus for those skilled in the art.

[0005] Summary of the Invention

[0006] This application is made in view of the above-mentioned problems, and one of its purposes is to provide a composite current collector with a specific structure that can improve the current flow capacity of the tab and make the battery have higher energy density and better safety.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a composite current collector, including a first metal layer, a second metal layer and a first bonding layer, the first metal layer including a first main body region and a first pole lug region, the first pole lug region is located at the end of the first metal layer, the second metal layer including a second main body region and a second pole lug region, the second pole lug region is located at the end of the second metal layer, the first main body region and the second main body region are connected by the first bonding layer, the thickness of the first pole lug region is greater than the thickness of the first main body region, and the first pole lug region extends toward the second pole lug region.

[0008] The composite current collector of the present application forms a first tab region at the end of the first metal layer and a second tab region at the end of the second metal layer, connecting the first and second main body regions via a first adhesive layer. The thickness of the first tab region is greater than that of the first main body region, and the first tab region extends toward the second tab region. The first and second tab regions of this composite current collector can be directly welded together as tabs, eliminating the need for a transfer welding process. This enhances the tab conductivity and resolves the issue of insufficient current flow capacity at the tab weld. Furthermore, since only the first tab region is thickened, without requiring the first main body region, this allows the battery to pass a needle penetration test, improving battery safety and increasing battery energy density.

[0009] In any embodiment, a first groove is provided at one end of the first tab region extending toward the second tab region, the first groove extending from one side of the first tab region proximate to the first main body region to the other side. This arrangement forms a stepped gap between the first tab region and the second tab region, which can form a stepped bonding layer after being filled with adhesive.

[0010] In any embodiment, the thickness of the second tab region is greater than that of the second main body region, and the second tab region extends toward the first tab region. Thus, the first tab region and the second tab region extend toward each other, which can significantly improve the tab current capacity.

[0011] In any embodiment, a second groove is provided at one end of the second tab region extending toward the first tab region, and the second groove extends from one side of the second tab region closest to the second main body region to the other side. This facilitates forming a stepped gap between the first tab region and the second tab region.

[0012] In any embodiment, a second adhesive layer is provided between the first tab region and the second tab region, and the second adhesive layer at least partially fills the gap between the first tab region and the second tab region. In this way, the stability of the first tab region and the second tab region can be improved, and the problems of cracks and broken belts in the first tab region and the second tab region during the subsequent cold pressing process can be avoided. On the one hand, the second adhesive layer can provide support for the first tab region and the second tab region, and on the other hand, it does not affect the effect of direct welding. During direct welding, the part of the tab region without the second adhesive layer can be directly welded, and the second adhesive layer can also diffuse into the blank area at the position where the second adhesive layer is present, so that the first tab region and the second tab region can be connected by welding.

[0013] In any embodiment, a second adhesive layer is provided between the first and second tab regions, the second adhesive layer at least partially filling the gap between the first and second tab regions; and the thickness of the second adhesive layer in the first and / or second grooves is greater than the thickness of the second adhesive layer in other locations. This provides better support for the first and second tab regions.

[0014] In any embodiment, the thickness of the second adhesive layer located in the first groove and / or the second groove is 0.5 μm to 5 μm; optionally, the thickness of the second adhesive layer located in the first groove and / or the second groove is 0.5 μm to 3 μm. This thickness is not too thick, which can improve the effect of direct tab welding.

[0015] In any embodiment, the thickness of the second adhesive layer at other locations is less than 0.5 μm. By controlling the thickness of the second adhesive layer at locations other than the first and second grooves to be less than 0.5 μm, ultrasonic welding can directly penetrate the second adhesive layer at these locations without affecting the welding effect.

[0016] In any embodiment, the ratio of the total thickness of the first and second tab regions to the thickness of the second adhesive layer in the first and / or second grooves is greater than or equal to 2. Optionally, the ratio of the total thickness of the first and second tab regions to the thickness of the second adhesive layer in the first and / or second grooves is 2 to 20. This can also better ensure the ultrasonic welding effect without significantly reducing the energy density.

[0017] In any embodiment, the ratio of the width of the first groove to the width of the first tab region is 0.05-0.5; the ratio of the width of the second adhesive layer in the first groove to the width of the first tab region is 0.05-0.5; the ratio of the width of the second groove to the width of the second tab region is 0.05-0.5; and the ratio of the width of the second adhesive layer in the second groove to the width of the second tab region is 0.05-0.5. This provides good support for the tab region without affecting the direct welding effect.

[0018] In any embodiment, the side of the second tab region adjacent to the second main body region contacts the first adhesive layer. This allows the sidewalls of the second tab region to also be supported by the first adhesive layer, particularly the root portion of the second tab region. This prevents the root portion from being damaged during subsequent cold pressing and other processing, thereby preventing the tab from becoming less conductive and deteriorating battery performance.

[0019] In any embodiment, the first tab region is connected to the second tab region. This allows the first tab region and the second tab region to be directly connected and electrically conductive, resulting in the first and second tab regions being in the same state as normal metal foil tabs. This can further improve battery performance, tab current capacity, and fast charging capabilities, and allows for direct ultrasonic welding, eliminating the need for transfer welding.

[0020] In any embodiment, the second adhesive layer is connected to the first adhesive layer. This can further improve the stability of the junction and enhance the crack resistance of the roots of the first and second tab regions during cold pressing, thereby improving battery performance.

[0021] In any embodiment, the first tab region is in contact with the first adhesive layer on a side adjacent to the first main body region. This allows the sidewalls of the first tab region, and in particular, the root portion of the first tab region, to be supported by the first adhesive layer. This prevents the root portion from being damaged during subsequent cold pressing and other processing, thereby preventing deterioration in the tab conductivity and thus preventing degradation in battery performance.

[0022] In any embodiment, the first metal layer includes multiple first body regions, each separated by a third tab region; the second metal layer includes multiple second body regions, each separated by a fourth tab region; the thickness of the third tab region is greater than that of the first body region, and the third tab region extends toward the fourth tab region. Thus, three or more tab welding regions can be formed on a single first and second metal layer, creating a battery structure with more tabs.

[0023] In any embodiment, the thickness of the fourth tab region is greater than the thickness of the second main body region, and the fourth tab region extends toward the third tab region. Thus, the third and fourth tab regions extend toward each other, which can significantly improve the tab current capacity.

[0024] In any embodiment, the sidewall of the fourth tab region is in contact with the first adhesive layer. This allows the sidewall of the fourth tab region to also be supported by the first adhesive layer, particularly the root portion of the fourth tab region. This prevents the root portion from being damaged during subsequent cold pressing and other processing, thereby preventing the tab from becoming less conductive and deteriorating battery performance.

[0025] In any embodiment, the third tab region is connected to the fourth tab region. This allows the third tab region and the fourth tab region to be directly connected and electrically connected, resulting in an electrical conduction state. This allows the third and fourth tab regions to behave like normal metal foil tabs, thereby improving battery performance, tab current capacity, and fast charging capabilities. Furthermore, ultrasonic welding can be performed directly, eliminating the need for transfer welding.

[0026] In any embodiment, a third bonding layer is provided between the third tab region and the fourth tab region, and the third bonding layer at least partially fills the gap between the third tab region and the fourth tab region. In this way, the stability of the third tab region and the fourth tab region can be improved, and the problems of cracks and broken bands in the third tab region and the fourth tab region during the subsequent cold pressing process can be avoided. On the one hand, the third bonding layer can provide support for the third tab region and the fourth tab region, and on the other hand, it does not affect the effect of direct welding. During direct welding, the part of the tab region without the third bonding layer can be directly welded, and the third bonding layer can also diffuse into the blank area at the position where the third bonding layer is present, so that the third tab region and the fourth tab region can be connected by welding.

[0027] In any embodiment, the third bonding layer partially fills the gap between the third tab region and the fourth tab region, thereby making it easier to process the third tab region and the fourth tab region as tabs by direct welding.

[0028] In any embodiment, the third adhesive layer is connected to the first adhesive layer. This can further improve the stability of the junction and enhance the crack resistance of the roots of the third and fourth tab regions during cold pressing, thereby improving battery performance.

[0029] In any embodiment, the sidewalls of the third tab region are in contact with the first adhesive layer. This allows the sidewalls of the third tab region to also be supported by the first adhesive layer, particularly the root portion of the third tab region. This prevents the root portion from being damaged during subsequent cold pressing and other processing, thereby preventing the tab conductivity from deteriorating and thus preventing degradation of battery performance.

[0030] In any embodiment, the thickness of the third adhesive layer is 0.5 μm to 5 μm; optionally, the thickness of the third adhesive layer is 0.5 μm to 3 μm.

[0031] In any embodiment, the sum of the thickness of the first tab region and the thickness of the second tab region is greater than or equal to 7 μm. Thus, making the sum of the thickness of the first tab region and the thickness of the second tab region greater than or equal to 7 μm facilitates direct ultrasonic welding and better ensures the flow conductivity of the tab region.

[0032] In any embodiment, the sum of the thickness of the first tab region and the thickness of the second tab region is 7 μm to 15 μm. When the sum of the thickness of the first tab region and the second tab region is within this range, ultrasonic welding is more convenient, improving flow conductivity without reducing energy density. If the sum of the thickness of the first tab region and the second tab region is too large, it will not significantly improve flow conductivity and may even reduce energy density.

[0033] In any embodiment, the sum of the thickness of the third tab region and the thickness of the fourth tab region is greater than or equal to 7 μm. Thus, making the sum of the thickness of the third tab region and the thickness of the fourth tab region greater than or equal to 7 μm also facilitates direct ultrasonic welding and better ensures the flow conductivity of the tab region.

[0034] In any embodiment, the sum of the thickness of the third tab region and the thickness of the fourth tab region is 7 μm to 15 μm. When the sum of the thickness of the third and fourth tab regions is within this range, ultrasonic welding is more convenient, improving flow conductivity without reducing energy density. If the sum of the thickness of the third and fourth tab regions is too large, it will not significantly improve flow conductivity and may even reduce energy density.

[0035] In any embodiment, the sum of the thicknesses of the first tab region and the second tab region is 5μm to 13μm greater than the sum of the thicknesses of the first main body region and the second main body region. Thus, thickening the first tab region and the second tab region can improve the flow capacity of the composite current collector and enhance fast-charging performance. Simultaneously, the first and second main body regions are relatively thin, enabling the battery to pass a needle penetration test and improving battery safety. Furthermore, reducing the total thickness of the first and second main body regions can also enhance the energy density of the battery. The total thickness of the first tab region and the second tab region should not be too thick, as this will not significantly improve fast-charging performance and will worsen energy density.

[0036] In any embodiment, the combined thickness of the third and fourth tab regions is 5 μm to 13 μm greater than the combined thickness of the first and second main body regions. Similarly, thickening the third and fourth tab regions can improve the flow capacity of the composite current collector and enhance fast-charging performance. Relatively thinning the first and second main body regions can enable the battery to pass a needle penetration test, improving battery safety. Furthermore, reducing the thickness of the first and second main body regions can also increase the battery's energy density.

[0037] In any embodiment, the first bonding layer comprises one or more of a particulate material and a conductive agent. The particulate material in the first bonding layer can effectively enhance the support function of the first bonding layer; and the conductive agent in the first bonding layer can effectively enhance the conductive properties of the first bonding layer.

[0038] In any embodiment, the second adhesive layer and / or the third adhesive layer may also contain one or more of the above-mentioned particulate materials and conductive agents, which can also improve the supporting function and conductive performance of the second adhesive layer and the third adhesive layer, respectively.

[0039] In any embodiment, the particulate material includes one or more of inorganic compound particles and metal particles.

[0040] In any embodiment, the inorganic compound particles include one or more of aluminum oxide, silicon carbide, silicon nitride, silicon oxide, calcium oxide, boehmite, titanium dioxide, zirconium dioxide, magnesium oxide, zinc oxide, barium sulfate, and boron carbide.

[0041] In any embodiment, the metal particles include an alloy of at least one or more of Cu, Al, Ni, Ti, Pt, Fe, Au, Co, Cr, W, Mo, Mg, Pb, In, and Sn.

[0042] In any embodiment, the conductive agent includes one or more of carbon nanotubes, conductive carbon, graphene, and conductive polymers.

[0043] In any embodiment, the sum of the mass proportions of the particulate material and the conductive agent in the first bonding layer is 20% to 70%.

[0044] In any embodiment, the binder in the first adhesive layer includes one or more of polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polyethylene grafted with carboxylic acid and its derivatives, polypropylene, polypropylene grafted with carboxylic acid and its derivatives, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polymethyl methacrylate, polyethylene glycol, polysulfur nitride, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, polypyrrole, polythiophene, polyaniline, and phenolic resin.

[0045] In any embodiment, the binder in the first adhesive layer may also be a derivative, a cross-linked product or a copolymer of the above-mentioned binders.

[0046] In any embodiment, the first metal layer and the second metal layer each include at least one of Cu, Al, Ni, Ti, Pt, Fe, Au, Co, Cr, W, Mo, Mg, Pb, In, Sn or an alloy thereof.

[0047] The second aspect of the present application provides a secondary battery comprising the composite current collector of the first aspect of the present application, thereby providing the secondary battery with good current capacity, high energy density and good safety.

[0048] A third aspect of the present application provides an electrical device comprising the secondary battery of the second aspect of the present application.

[0049] The composite current collector of the present application forms a first tab region at the end of the first metal layer and a second tab region at the end of the second metal layer, connecting the first and second main body regions via a first adhesive layer. The thickness of the first tab region is greater than that of the first main body region, and the first tab region extends toward the second tab region. The first and second tab regions of the composite current collector can be directly welded as tabs, eliminating the need for a transfer welding process. This enhances the tab conductivity and resolves the issue of insufficient current flow capacity at the tab welds. Furthermore, since only the first tab region is thickened, without requiring the first main body region, the battery can pass a needle penetration test, improving battery safety and increasing its energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to better describe and illustrate the embodiments and / or examples of the present application, reference may be made to one or more of the accompanying drawings. The additional details or examples used to describe the accompanying drawings should not be considered as limiting the scope of the disclosed application, the presently described embodiments and / or examples, and any of the best modes currently understood for these applications.

[0051] FIG1 is a schematic diagram of a composite current collector according to an embodiment of the present application;

[0052] FIG2 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0053] FIG3 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0054] FIG4 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0055] FIG5 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0056] FIG6 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0057] FIG7 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0058] FIG8 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0059] FIG9 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0060] FIG10 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0061] FIG11 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0062] FIG12 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0063] FIG13 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0064] FIG14 is a schematic diagram of a composite current collector according to another embodiment of the present application;

[0065] FIG15 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0066] FIG16 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG15 ;

[0067] FIG17 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0068] Description of reference numerals:

[0069] 1. First metal layer; 2. Second metal layer; 3. First bonding layer; 4. First groove; 5. Secondary battery; 6. Electrical device; 7. Second groove; 8. Second bonding layer; 9. Third bonding layer; 10. Granular material; 11. First main body region; 12. First tab region; 13. Third tab region; 14. Conductive agent; 21. Second main body region; 22. Second tab region; 23. Fourth tab region; 51. Shell; 52. Electrode assembly; 53. Cover plate; 100. Composite current collector. DETAILED DESCRIPTION

[0070] Below, the embodiments of the separator, secondary battery, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0071] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0072] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0073] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0074] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0075] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0076] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0077] With the rapid development of secondary batteries, higher requirements are being placed on their current handling capacity, energy density, and safety performance. High-performance secondary batteries place high demands on composite current collectors. Therefore, the search for composite current collectors with even better performance is a key area of ​​focus for those skilled in the art. In conventional composite current collectors, the tabs must be welded to the current collector's metal layer through an additional transfer welding process. This not only introduces additional manufacturing costs, but also requires the use of additional metal foil, which reduces the battery's energy density and can easily lead to weld defects such as cold welds. Furthermore, in conventional composite current collectors, the metal foil in the tab and tab regions is the same thickness, limiting the current handling capacity and impacting the fast-charging performance of the battery cell. Improving the current handling capacity requires thickening the metal layer overall, which can compromise battery safety and reduce energy density. The inventors have discovered a composite current collector with a unique structure that improves current handling capacity, enabling batteries with higher energy density and improved safety.

[0078] Please refer to Figures 1 to 14. In some embodiments, the first aspect of the present application provides a composite current collector 100, including a first metal layer 1, a second metal layer 2 and a first bonding layer 3. The first metal layer 1 includes a first main body region 11 and a first pole lug region 12, and the first pole lug region 12 is located at the end of the first metal layer 1. The second metal layer 2 includes a second main body region 21 and a second pole lug region 22, and the second pole lug region 22 is located at the end of the second metal layer 2. The first main body region 11 and the second main body region 21 are connected through the first bonding layer 3. The thickness of the first pole lug region 12 is greater than the thickness of the first main body region 11, and the first pole lug region 12 extends toward the second pole lug region 22.

[0079] The composite current collector 100 of the present application forms a first tab region 12 at the end of the first metal layer 1 and a second tab region 22 at the end of the second metal layer 2, connecting the first main region 11 and the second main region 21 via a first adhesive layer 3. The thickness of the first tab region 12 is greater than that of the first main region 11, and the first tab region 12 extends toward the second tab region 22. The first tab region 12 and the second tab region 22 of the composite current collector 100 can be directly welded as tabs, eliminating the need for a transfer welding process. This enhances the tab conductivity and solves the problem of insufficient current flow capacity at the tab weld. Furthermore, since only the first tab region 12 is thickened, without thickening the first main region 11, the battery can pass the needle penetration test, improving battery safety and increasing battery energy density.

[0080] It can be understood that the composite current collector 100 of the present application connects the first main body region 11 and the second main body region 21 through the first adhesive layer 3 , and the first tab region 12 and the second tab region 22 form regions protruding from the first adhesive layer 3 .

[0081] In some embodiments, the thickness of the second tab region 22 is greater than the thickness of the second main body region 21, and the second tab region 22 extends toward the first tab region 12. Thus, the first tab region 12 and the second tab region 22 extend toward each other, which can significantly improve the tab current capacity.

[0082] In some embodiments, a first groove 4 is provided at one end of the first tab region 12 extending toward the second tab region 22. The first groove 4 extends from one side of the first tab region 12 close to the first main body region 11 to the other side. This arrangement can form a stepped gap between the first tab region 12 and the second tab region 22. After filling with adhesive, a stepped bonding layer can be formed, thereby providing better support for the tab region.

[0083] In some embodiments, a second groove 7 is provided at one end of the second tab region 22 extending toward the first tab region 12. The second groove 7 extends from one side of the second tab region 22 close to the second main body region 21 to the other side. This is more conducive to forming a stepped gap between the first tab region 12 and the second tab region 22. After the stepped gap is filled with adhesive, it can better provide support for the tab region.

[0084] In some embodiments, a second bonding layer 8 is provided between the first tab region 12 and the second tab region 22, and the second bonding layer 8 at least partially fills the gap between the first tab region 12 and the second tab region 22. In this way, the stability of the first tab region 12 and the second tab region 22 can be improved, and the problems of cracks and broken belts in the first tab region 12 and the second tab region 22 during the subsequent cold pressing process can be avoided. On the one hand, the second bonding layer 8 can provide support for the first tab region 12 and the second tab region 22, and on the other hand, it does not affect the effect of direct welding. During direct welding, the part of the tab region without the second bonding layer 8 can be directly welded, and the second bonding layer 8 at the position where the second bonding layer 8 is present can also diffuse into the blank area so that the first tab region 12 and the second tab region 22 can be connected by welding.

[0085] It can be understood that the second adhesive layer 8 can completely fill the gap between the first tab area 12 and the second tab area 22 ; or it can only partially fill the gap between the first tab area 12 and the second tab area 22 .

[0086] In some embodiments, the second bonding layer 8 partially fills the gap between the first tab region 12 and the second tab region 22. This makes it easier to process the first tab region 12 and the second tab region 22 as tabs by direct welding.

[0087] In some embodiments, a second adhesive layer 8 is provided between the first tab region 12 and the second tab region 22. The second adhesive layer 8 at least partially fills the gap between the first tab region 12 and the second tab region 22. Furthermore, the thickness of the second adhesive layer 8 located in the first groove 4 and / or the second groove 7 (as shown in the region A in FIG5 ) is greater than the thickness of the second adhesive layer 8 in other locations (as shown in the region B in FIG5 ). This provides better support for the first tab region 12 and the second tab region 22.

[0088] In some embodiments, the thickness of the second adhesive layer 8 located in the first groove 4 and / or the second groove 7 is 0.5 μm to 5 μm; alternatively, the thickness of the second adhesive layer 8 located in the first groove 4 and / or the second groove 7 is 0.5 μm to 3 μm. In this way, the thickness is not too thick, which can improve the effect of direct tab welding.

[0089] It can be understood that the thickness of the second adhesive layer 8 located at the first groove 4 and / or the second groove 7 can be but is not limited to 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm.

[0090] In some embodiments, the thickness of the second adhesive layer 8 at other locations is less than 0.5 μm. By controlling the thickness of the second adhesive layer 8 at locations other than the first groove 4 and the second groove 7 to be less than 0.5 μm, ultrasonic welding can directly penetrate the second adhesive layer 8 at these locations without affecting the welding effect.

[0091] It can be understood that the thickness of the second adhesive layer 8 at other locations outside the first groove 4 and the second groove 7 can be but is not limited to 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, or 0.45 μm.

[0092] In some embodiments, the ratio of the total thickness of the first tab region 12 and the second tab region 22 to the thickness of the second adhesive layer 8 in the first groove 4 and / or the second groove 7 is greater than or equal to 2; alternatively, the ratio of the total thickness of the first tab region 12 and the second tab region 22 to the thickness of the second adhesive layer 8 in the first groove 4 and / or the second groove 7 is 2 to 20. This can also better ensure the effect of ultrasonic welding without significantly reducing the energy density.

[0093] It can be understood that the ratio of the total thickness of the first tab area 12 and the second tab area 22 to the thickness of the second adhesive layer 8 located in the first groove 4 and / or the second groove 7 can be but is not limited to 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20.

[0094] In some embodiments, the ratio of the width of the first groove 4 to the width of the first tab region 12 is 0.05-0.5; the ratio of the width of the second adhesive layer in the first groove to the width of the first tab region is 0.05-0.5; the ratio of the width of the second groove to the width of the second tab region is 0.05-0.5; and the ratio of the width of the second adhesive layer in the second groove to the width of the second tab region is 0.05-0.5. This provides good support for the tab region without affecting the effect of direct welding.

[0095] It can be understood that the ratio of the width of the first groove 4 to the width of the first tab region 12 can be, but is not limited to, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, or 0.5. The ratio of the width of the second groove 7 to the width of the second tab region 22 can be, but is not limited to, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, or 0.5.

[0096] In some embodiments, the surface of the first main body region 11 facing away from the second main body region 21 remains flush with the surface of the first pole tab region 12 facing away from the second pole tab region 22; the surface of the second main body region 21 facing away from the first main body region 11 remains flush with the surface of the second pole tab region 22 facing away from the first pole tab region 12.

[0097] In some embodiments, the side of the second tab region 22 adjacent to the second main body region 21 is connected to the first adhesive layer 3. This allows the sidewalls of the second tab region 22 to be supported by the first adhesive layer 3, particularly the root portion of the second tab region 22. This prevents the root portion from being damaged during subsequent cold pressing and other processing steps, thereby preventing the tab conductivity from deteriorating and thus preventing deterioration in battery performance.

[0098] In some embodiments, the first tab region 12 is connected to the second tab region 22. Thus, the first tab region 12 and the second tab region 22 are directly connected and electrically conductive, presenting an electrically conductive state. This allows the first tab region 12 and the second tab region 22 to be in the same state as a normal metal foil tab, thereby further improving battery performance, tab current capacity, and fast charging capability. Furthermore, ultrasonic welding can be performed directly, eliminating the need for a transfer welding process.

[0099] In some embodiments, the second adhesive layer 8 is connected to the first adhesive layer 3. This can further improve the stability of the junction and enhance the crack resistance of the roots of the first tab region 12 and the second tab region 22 during the cold pressing process, thereby improving battery performance.

[0100] It is understood that the second adhesive layer 8 and the first adhesive layer 3 can be made of the same material or different materials; the second adhesive layer 8 and the first adhesive layer 3 can be made separately and connected to each other, or they can be integrally formed. Optionally, the second adhesive layer 8 and the first adhesive layer 3 are made of the same material and integrally formed.

[0101] In some embodiments, the first tab region 12 is connected to the first adhesive layer 3 on one side thereof that is close to the first main body region 11. Thus, the sidewalls of the first tab region 12 are also supported by the first adhesive layer 3, and in particular, the root portion of the first tab region 12 is supported by the first adhesive layer 3. This prevents the root portion from being damaged during subsequent cold pressing and other processing, thereby preventing the tab conductivity from deteriorating and thus preventing deterioration of battery performance.

[0102] In some embodiments, the first metal layer 1 includes multiple first body regions 11, each separated by a third tab region 13. The second metal layer 2 includes multiple second body regions 21, each separated by a fourth tab region 23. The thickness of the third tab region 13 is greater than that of the first body region 11, and the third tab region 13 extends toward the fourth tab region 23. Thus, more than three tab welding regions can be formed on a single first metal layer 1 and second metal layer 2, forming a battery structure with more tabs.

[0103] It is understood that the number of first main body regions 11 in the first metal layer 1 can be two or more, correspondingly forming one or more third tab regions 13. Similarly, the number of second main body regions 21 in the second metal layer 2 can also be two or more, correspondingly forming one or more fourth tab regions 23. It should be noted that the number of third tab regions 13 and fourth tab regions 23 should be consistent, and the positions of the third tab regions 13 and fourth tab regions 23 should correspond to each other.

[0104] In some embodiments, the thickness of the fourth tab region 23 is greater than the thickness of the second main body region 21, and the fourth tab region 23 extends toward the third tab region 13. Thus, the third tab region 13 and the fourth tab region 23 extend toward each other, which can significantly improve the tab current capacity.

[0105] In some embodiments, the sidewalls of the fourth tab region 23 are connected to the first adhesive layer 3. In this way, the sidewalls of the fourth tab region 23 are also supported by the first adhesive layer 3, and in particular, the root of the fourth tab region 23 is supported by the first adhesive layer 3. This prevents the root from being damaged during subsequent cold pressing and other processing, thereby preventing the tab conductivity of the battery from deteriorating and thus avoiding deterioration of battery performance.

[0106] In some embodiments, the third tab region 13 is connected to the fourth tab region 23. Thus, the third tab region 13 and the fourth tab region 23 are directly connected and electrically connected, presenting an electrically conductive state. This allows the third tab region 13 and the fourth tab region 23 to present the same state as a normal metal foil tab, thereby further improving battery performance, tab current capacity, and fast charging capability. Furthermore, ultrasonic welding can be performed directly, eliminating the need for a transfer welding process.

[0107] In some embodiments, a third bonding layer 9 is provided between the third tab region 13 and the fourth tab region 23, and the third bonding layer 9 at least partially fills the gap between the third tab region 13 and the fourth tab region 23. In this way, the stability of the third tab region 13 and the fourth tab region 23 can be improved, and the problems of cracks and broken bands in the third tab region 13 and the fourth tab region 23 during the subsequent cold pressing process can be avoided. On the one hand, the third bonding layer 9 can provide support for the third tab region 13 and the fourth tab region 23, and on the other hand, it does not affect the effect of direct welding. During direct welding, the part of the tab region without the third bonding layer 9 can be directly welded, and the third bonding layer 9 at the position where the third bonding layer 9 is present can also diffuse into the blank area so that the third tab region 13 and the fourth tab region 23 can be connected by welding.

[0108] It is understandable that the third bonding layer 9 may completely fill the gap between the third tab region 13 and the fourth tab region 23 ; or may only partially fill the gap between the third tab region 13 and the fourth tab region 23 .

[0109] In some embodiments, the third bonding layer 9 partially fills the gap between the third tab region 13 and the fourth tab region 23. This makes it easier to process the third tab region 13 and the fourth tab region 23 as tabs by direct welding.

[0110] In some embodiments, the third adhesive layer 9 is connected to the first adhesive layer 3. This can further improve the stability of the junction and enhance the crack resistance of the roots of the third and fourth tab regions 13 and 23 during the cold pressing process, thereby improving battery performance.

[0111] It is understood that the third adhesive layer 9 and the first adhesive layer 3 can be made of the same material or different materials; the third adhesive layer 9 and the first adhesive layer 3 can be made separately and connected to each other, or they can be integrally formed. Optionally, the third adhesive layer 9 and the first adhesive layer 3 are made of the same material and integrally formed.

[0112] In some embodiments, the sidewalls of the third tab region 13 are connected to the first adhesive layer 3. In this way, the sidewalls of the third tab region 13 are also supported by the first adhesive layer 3, and in particular, the root of the third tab region 13 is supported by the first adhesive layer 3. This prevents the root from being damaged during subsequent cold pressing and other processing, thereby preventing the tab conductivity of the battery from deteriorating and thus avoiding deterioration of battery performance.

[0113] In some embodiments, the thickness of the third adhesive layer 9 is 0.5 μm to 5 μm. Optionally, the thickness of the third adhesive layer 9 is 0.5 μm to 3 μm. It is understood that the thickness of the third adhesive layer 9 can be, but is not limited to, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, or 5 μm.

[0114] In some embodiments, the sum of the thickness of the first tab region 12 and the thickness of the second tab region 22 is greater than or equal to 7 μm. Thus, by making the sum of the thickness of the first tab region 12 and the thickness of the second tab region 22 greater than or equal to 7 μm, ultrasonic welding can be performed more conveniently and the flow conductivity of the tab region can be better ensured.

[0115] In some embodiments, the sum of the thicknesses of the first tab region 12 and the second tab region 22 is 7 μm to 15 μm. A sum of the thicknesses of the first tab region 12 and the second tab region 22 within this range facilitates ultrasonic welding, improves flow conductivity, and does not reduce energy density. If the sum of the thicknesses of the first tab region 12 and the second tab region 22 is too large, it will not significantly improve flow conductivity and may even reduce energy density.

[0116] In some embodiments, the sum of the thickness of the third tab region 13 and the thickness of the fourth tab region 23 is greater than or equal to 7 μm. Thus, making the sum of the thickness of the third tab region 13 and the thickness of the fourth tab region 23 greater than or equal to 7 μm also facilitates direct ultrasonic welding and better ensures the flow conductivity of the tab region.

[0117] In some embodiments, the sum of the thicknesses of the third tab region 13 and the fourth tab region 23 is 7 μm to 15 μm. When the sum of the thicknesses of the third tab region 13 and the fourth tab region 23 is within this range, ultrasonic welding can be more easily performed, improving flow conductivity without reducing energy density. If the sum of the thicknesses of the third tab region 13 and the fourth tab region 23 is too large, it will not significantly improve flow conductivity and may even reduce energy density.

[0118] It can be understood that the sum of the thickness of the first pole tab area 12 and the thickness of the second pole tab area 22 can be but not limited to 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm; the sum of the thickness of the third pole tab area 13 and the thickness of the fourth pole tab area 23 can be but not limited to 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm.

[0119] In some embodiments, the sum of the thicknesses of the first tab region 12 and the second tab region 22 is 5 μm to 13 μm greater than the sum of the thicknesses of the first main body region 11 and the second main body region 21. Thus, thickening the first tab region 12 and the second tab region 22 can improve the flow capacity of the composite current collector and enhance fast-charging performance. At the same time, the first main body region 11 and the second main body region 21 are relatively thin, enabling the battery to pass a needle penetration test and improving battery safety. Furthermore, reducing the thickness of the first main body region 11 and the second main body region 21 can also improve the energy density of the battery. The thicknesses of the first tab region 12 and the second tab region 22 should not be too thick either. Too much thickness will not significantly improve fast-charging performance and will worsen energy density.

[0120] It can be understood that the difference between the sum of the thicknesses of the first tab region 12 and the second tab region 22 and the sum of the thicknesses of the first main region 11 and the second main region 21 can be but is not limited to 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm.

[0121] In some embodiments, the combined thickness of the third tab region 13 and the fourth tab region 23 is 5 μm to 13 μm greater than the combined thickness of the first main body region 11 and the second main body region 21. Similarly, thickening the third tab region 13 and the fourth tab region 23 can improve the current flow capacity of the composite current collector 100 and enhance fast-charging performance. The relatively thin first main body region 11 and the second main body region 21 can enable the battery to pass a needle penetration test, improving battery safety. Furthermore, reducing the thickness of the first main body region 11 and the second main body region 21 can also increase the battery's energy density.

[0122] It can be understood that the difference between the sum of the thicknesses of the third tab region 13 and the fourth tab region 23 and the sum of the thicknesses of the first main region 11 and the second main region 21 can be but is not limited to 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, or 13μm.

[0123] It can be understood that the thicknesses of the first tab region 12 , the second tab region 22 , the third tab region 13 and the fourth tab region 23 may be the same or different; the thicknesses of the first main body region 11 and the second main body region 21 may be the same or different.

[0124] In some embodiments, the first bonding layer 3 includes one or more of a particulate material 10 and a conductive agent 14. Thus, the particulate material 10 included in the first bonding layer 3 can effectively enhance the support function of the first bonding layer 3; and the conductive agent 14 included in the first bonding layer 3 can effectively enhance the conductive performance of the first bonding layer 3.

[0125] It is understood that the first bonding layer 3 may include either or both of the particulate material 10 and the conductive agent 14. Furthermore, the second bonding layer 8 and / or the third bonding layer 9 may also include one or more of the above-mentioned particulate material 10 and conductive agent 14. This can also enhance the support function and conductive performance of the second bonding layer 8 and the third bonding layer 9, respectively.

[0126] In some embodiments, the particulate material 10 includes one or more of inorganic compound particles and metal particles. That is, the particulate material 10 can be inorganic compound particles or metal particles, or a mixed particulate material of inorganic compound particles and metal particles.

[0127] In some embodiments, the inorganic compound particles include one or more of aluminum oxide, silicon carbide, silicon nitride, silicon oxide, calcium oxide, boehmite, titanium dioxide, zirconium dioxide, magnesium oxide, zinc oxide, barium sulfate, and boron carbide. In other words, the inorganic compound particles can be any one of the above or a mixture of multiple of the above.

[0128] In some embodiments, the metal particles include alloys of at least one or more of Cu, Al, Ni, Ti, Pt, Fe, Au, Co, Cr, W, Mo, Mg, Pb, In, and Sn. That is, the metal particles may be any one of Cu, Al, Ni, Ti, Pt, Fe, Au, Co, Cr, W, Mo, Mg, Pb, In, and Sn particles; or may be mixed metal particles of any two or more of Cu, Al, Ni, Ti, Pt, Fe, Au, Co, Cr, W, Mo, Mg, Pb, In, and Sn particles; or may be alloy particles of any two or more of Cu, Al, Ni, Ti, Pt, Fe, Au, Co, Cr, W, Mo, Mg, Pb, In, and Sn.

[0129] In some embodiments, the conductive agent 14 includes one or more of carbon nanotubes, conductive carbon, graphene, and conductive polymers. In other words, the conductive agent 14 may include any one of carbon nanotubes, conductive carbon, graphene, and conductive polymers; or may include two or more of the carbon nanotubes, conductive carbon, graphene, and conductive polymers.

[0130] In some embodiments, the sum of the mass proportions of the particulate material 10 and the conductive agent 14 in the first bonding layer 3 is 20% to 70%. It is understood that the sum of the mass proportions of the particulate material 10 and the conductive agent 14 in the first bonding layer 3 may be, but is not limited to, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%. It is understood that the sum of the mass proportions of the particulate material 10 and the conductive agent 14 in the second bonding layer 8 and the third bonding layer 9 may also be 20% to 70%, respectively.

[0131] In some embodiments, the binder in the first bonding layer 3 includes one or more of polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polyethylene grafted with carboxylic acid and its derivatives, polypropylene, polypropylene grafted with carboxylic acid and its derivatives, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polymethyl methacrylate, polyethylene glycol, polysulfur nitride, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, polypyrrole, polythiophene, polyaniline, and phenolic resin.

[0132] It is understood that the adhesive in the first adhesive layer 8 can be any one of the adhesives listed above, or a mixture of two or more of the adhesives listed above. The adhesive in the second adhesive layer 8 and the third adhesive layer 9 can also be one or more of the adhesives listed above.

[0133] In some embodiments, the adhesive in the first adhesive layer 3 , the second adhesive layer 8 , and the third adhesive layer 9 may also be a derivative, a cross-linked product, or a copolymer of the types of adhesives listed above.

[0134] In some embodiments, the first metal layer 1 and the second metal layer 2 both include at least one of Cu, Al, Ni, Ti, Pt, Fe, Au, Co, Cr, W, Mo, Mg, Pb, In, and Sn, or an alloy thereof. That is, the first metal layer 1 and the second metal layer 2 can both use any one of Cu, Al, Ni, Ti, Pt, Fe, Au, Co, Cr, W, Mo, Mg, Pb, In, and Sn metal layers, or use two or more of them simultaneously. They can also use alloy metal layers of any two or more of Cu, Al, Ni, Ti, Pt, Fe, Au, Co, Cr, W, Mo, Mg, Pb, In, and Sn.

[0135] It should be noted that the first metal layer 1 and the second metal layer 2 in the composite current collector 100 of the present application can be finished metal layers; or one of the metal layers can be a finished metal layer, and the other metal layer can be prepared by vacuum vapor deposition, electroless plating, electroplating, and other processes during the preparation of the composite current collector 100.

[0136] In some embodiments, the composite current collector 100 of the present application is prepared by the following method:

[0137] The first tab region 12 of the first metal layer 1 is coated with glue for protection; the first main region 11 of the first metal layer 1 is chemically etched; an adhesive is applied to the first main region 11 of the first metal layer 1 and dried. After drying, the adhesive layer thickness is greater than the etching depth of the first main region 11, and inorganic compound particles are mixed into the adhesive; the second main region 21 of the second metal layer 2 is hot-pressed with the other side of the adhesive, at a hot-pressing temperature 5°C to 20°C above the melting point of the adhesive layer; the hot-pressing temperature is cured at 60°C to 80°C for 48h to 72h; and the first metal layer 1 and the second metal layer 2 are selectively etched and thinned. The second adhesive layer 8 and the third adhesive layer 9 in the composite current collector 100 can be formed by the adhesive layer overflowing during the hot-pressing process.

[0138] In some embodiments, the composite current collector 100 of the present application is prepared by the following method:

[0139] The first tab region 12 of the first metal layer 1 is coated with glue for protection; the first main region 11 of the first metal layer 1 is chemically etched; an adhesive is applied to the first main region 11 of the first metal layer 1 and dried, wherein the thickness of the adhesive layer after drying is greater than the etching depth of the first main region 11, and inorganic compound particles are mixed in the adhesive; the second metal layer 2 is formed on the other side of the adhesive layer by at least one of vacuum vapor deposition, chemical plating, and electroplating, with the second tab region 22 of the second metal layer 2 being directly connected and conductive to the first tab region 12 of the first metal layer 1; hot pressing is performed; and curing is performed at 60°C to 80°C for 48 hours to 72 hours. The second adhesive layer 8 and the third adhesive layer 9 in the composite current collector 100 can be formed by the adhesive layer overflowing during the hot pressing process.

[0140] In some embodiments, the second aspect of the present application provides a secondary battery, which includes the composite current collector 100 of the first aspect of the present application. As a result, the secondary battery has good current capacity, high energy density, and good safety.

[0141] In some embodiments, the second aspect of the present application provides an electric device, which includes the secondary battery of the second aspect of the present application. Specifically, the secondary battery can serve as a power source for the electric device to provide an operating voltage for the electric device.

[0142] The secondary battery and the electric device of the present application will be described below with reference to the accompanying drawings as appropriate.

[0143] Unless otherwise specified, the components, material types, or contents of the batteries mentioned are applicable to both lithium-ion secondary batteries and sodium-ion secondary batteries.

[0144] In one embodiment of the present application, a secondary battery is provided.

[0145] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.

[0146]

Positive electrode

[0147] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0148] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.

[0149] The positive electrode sheet in the present application may adopt the composite current collector of the first aspect of the present application.

[0150] In some embodiments, the positive electrode active material may include a positive electrode active material for a battery known in the art.

[0151] As an example, the positive electrode active material of a lithium-ion secondary battery may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0152] As an example, the positive electrode active material of a sodium ion secondary battery may include at least one of the following materials: a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.

[0153] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Sodium transition metal oxide is, for example, Na x MO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1.

[0154] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n-A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si; n represents (YO4) n- valence.

[0155] Polyanionic compounds can also be sodium ions, transition metal ions, tetrahedral (YO4) n- A class of compounds containing anion units and halogen anions. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be at least one of P, S, and Si, and n represents (YO4) n- valence state; the halogen may be at least one of F, Cl and Br.

[0156] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n- Anion unit, polyhedron unit (ZO y ) m+ and an optional halogen anion. Y can be at least one of P, S and Si, and n represents (YO4) n- valence state; Z represents a transition metal, which may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce, and m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl and Br.

[0157] Polyanionic compounds include NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, abbreviated as NVP), Na4Fe3(PO4)2(P2O7), NaM'PO4F (M' is one or more of V, Fe, Mn and Ni) and Na3(VO y )2(PO4)2F 3-2y At least one of (0≤y≤1).

[0158] Prussian blue compounds can be sodium ions, transition metal ions and cyanide ions (CN - ) compounds. The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.

[0159] The weight ratio of the positive electrode active material in the positive electrode film layer is 80 wt % to 100 wt %, based on the total weight of the positive electrode film layer.

[0160] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0% to 20% by weight, based on the total weight of the positive electrode film layer.

[0161] In some embodiments, the positive electrode film layer may further optionally include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0% to 20% by weight, based on the total weight of the positive electrode film layer.

[0162] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40wt% to 80wt%, and the viscosity at room temperature is adjusted to 5000mPa·s to 25000mPa·s, the positive electrode slurry is coated on the surface of the positive electrode collector, and after drying, the positive electrode sheet is formed by cold rolling; the positive electrode powder coating unit area density is 150mg / m 2 ~350 mg / m 2 The compaction density of the positive electrode is 3.0g / cm 3 ~3.6g / cm 3 , optional 3.3g / cm 3 ~3.5g / cm 3 .

[0163] The calculation formula of the compacted density is:

[0164] Compaction density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).

[0165] The mass M of the positive electrode active material per unit area of ​​the positive electrode membrane can be obtained by weighing using a standard balance.

[0166] The thickness T of the positive electrode film can be measured using a micrometer, for example, a Mitutoyo 293-100 with an accuracy of 0.1 μm. It should be noted that the thickness of the positive electrode film described in this application refers to the thickness of the positive electrode film in the positive electrode sheet after cold pressing and used in battery assembly.

[0167]

Negative electrode

[0168] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0169] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0170] The negative electrode sheet in the present application may adopt the composite current collector of the first aspect of the present application.

[0171] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art.

[0172] As an example, the negative electrode active material of a lithium-ion secondary battery may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0173] As an example, the negative electrode active material of a sodium ion secondary battery is generally a hard carbon material, a two-dimensional metal carbide or a nitride. Preferably, the negative electrode active material of a sodium ion secondary battery is generally a hard carbon material.

[0174] The weight ratio of the negative electrode active material in the negative electrode film layer is 70 weight % to 100 weight %, based on the total weight of the negative electrode film layer.

[0175] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode film layer is 0% to 30% by weight, based on the total weight of the negative electrode film layer.

[0176] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0% to 20% by weight, based on the total weight of the negative electrode film layer.

[0177] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (e.g., sodium carboxymethyl cellulose (CMC-Na)). The weight ratio of the other additives in the negative electrode film layer is 0 wt % to 15 wt %, based on the total weight of the negative electrode film layer.

[0178] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the solid content of the negative electrode slurry is 30wt% to 70wt%, and the viscosity at room temperature is adjusted to 2000mPa·s to 10000mPa·s; the obtained negative electrode slurry is coated on the negative electrode current collector, and after a drying process, cold pressing, such as rolling, is performed to obtain the negative electrode sheet. The negative electrode powder coating unit area density is 75mg / m 2 ~220 mg / m 2 , the compaction density of the negative electrode is 1.2g / m 3 ~2.0g / m 3 .

[0179] The mass M of the negative electrode active material per unit area of ​​the negative electrode membrane can be obtained by weighing using a standard balance.

[0180] The thickness T of the negative electrode film can be measured using a micrometer, such as a Mitutoyo 293-100 with an accuracy of 0.1 μm. It should be noted that the thickness of the negative electrode film described in this application refers to the thickness of the negative electrode film after cold pressing and compaction and used in the negative electrode sheet assembled into the battery.

[0181] Electrolytes

[0182] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0183] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0184] In some embodiments, the electrolyte salt of the lithium ion secondary battery can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0185] The electrolyte salt of the sodium ion secondary battery can be selected from one or more of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, and sodium chloride.

[0186] The concentration of the electrolyte salt is usually 0.5-5 mol / L.

[0187] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).

[0188] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0189]

Isolation film

[0190] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0191] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0192] In some embodiments, the isolation film has a thickness of 6 μm to 40 μm, and may optionally be 12 μm to 20 μm.

[0193] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0194] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0195] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0196] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG15 shows a secondary battery 5 having a square structure as an example.

[0197] In some embodiments, referring to Figure 16, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0198] In some embodiments, the secondary batteries 5 can be assembled into a battery module. The number of secondary batteries 5 contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0199] In the battery module, the plurality of secondary batteries 5 can be arranged in sequence along the length of the battery module. Of course, they can also be arranged in any other manner. Furthermore, the plurality of secondary batteries 5 can be fixed by fasteners.

[0200] Optionally, the battery module may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0201] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0202] A battery pack may include a battery box and multiple battery modules disposed within the box. The battery box comprises an upper case and a lower case. The upper case can be placed over the lower case to form an enclosed space for accommodating the battery modules. The multiple battery modules can be arranged in any manner within the battery box.

[0203] In addition, the present application also provides an electrical device, which includes the secondary battery provided in the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0204] As the electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0205] Figure 17 shows an example of an electric device 6. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the electric device 6's requirements for high power and high energy density of secondary batteries, a battery pack or battery module can be used.

[0206] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0207] Example

[0208] In order to make the technical problems, technical solutions and beneficial effects solved by this application clearer, the application will be further described in detail below with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of this application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present application and its applications. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0209] If no specific techniques or conditions are specified in the examples, the experiments were carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. All reagents or instruments used without specifying the manufacturer are commercially available conventional products.

[0210] 1. Current Collector Preparation Example

[0211] Current Collector Preparation Example 1:

[0212] S1. Take a first aluminum foil, apply a protective adhesive (PMMA) to the first tab area of ​​the first aluminum foil; etch the first main body area of ​​the first aluminum foil with a NaOH solution; and then remove the protective adhesive with acetone;

[0213] S2. Prepare a bonding layer slurry, wherein the binder is maleic anhydride-modified polypropylene, the particulate material is metallic copper particles, and the conductive agent is carbon nanotubes. Dissolve 40% of the binder, 40% of the metallic copper particles, and 20% of the carbon nanotubes in an organic solvent in a mass ratio to prepare a bonding layer slurry with a solid content of 50%;

[0214] S3. Apply the above-mentioned adhesive layer slurry to the first main body area of ​​the first aluminum foil and dry it at 80°C to 100°C; hot-press the second aluminum foil on the surface of the adhesive facing away from the first aluminum foil, so that the first tab area of ​​the first aluminum foil extends toward the second tab area of ​​the second aluminum foil. The hot-pressing temperature is about 180°C (the melting point of the adhesive is about 163°C). The pressure is controlled so that the adhesive layer diffuses from the first main body area to the first tab area; and the mixture is cured at 70°C for 72 hours.

[0215] S4. Optionally, coating a protective adhesive layer (PMMA) on the areas of the first and second aluminum foils that do not require thinning according to thickness requirements, and chemically thinning the surface of the second aluminum foil facing away from the adhesive layer; then removing the protective adhesive with acetone;

[0216] S5. Optionally, according to thickness requirements, a protective adhesive layer (PMMA) is coated on the areas of the first aluminum foil and the second aluminum foil that do not need to be thinned, the surface of the first aluminum foil facing away from the adhesive layer is etched, and then the protective adhesive is removed with acetone to obtain a composite current collector.

[0217] Current Collector Preparation Example 2:

[0218] S1. Take a first aluminum foil, apply a protective adhesive (PMMA) to the first tab area of ​​the first aluminum foil; etch the first main body area of ​​the first aluminum foil with a NaOH solution; and then remove the protective adhesive with acetone;

[0219] S2, applying a protective glue (PMMA) to the non-groove area of ​​the first tab; etching the first main body area of ​​the first aluminum foil and the groove area of ​​the first tab with a NaOH solution; and then removing the protective glue with acetone;

[0220] S3. Prepare a bonding layer slurry, wherein the binder is maleic anhydride-modified polypropylene, the particulate material is metallic copper particles, and the conductive agent is carbon nanotubes. Dissolve 40% of the binder, 40% of the metallic copper particles, and 20% of the carbon nanotubes in an organic solvent in a mass ratio to prepare a bonding layer slurry with a solid content of 50%;

[0221] S4. Apply the above-mentioned adhesive layer slurry to the first main body area of ​​the first aluminum foil and dry it at 80°C to 100°C; hot-press the second aluminum foil on the surface of the adhesive facing away from the first aluminum foil, so that the first tab area of ​​the first aluminum foil extends toward the second tab area of ​​the second aluminum foil. The hot-pressing temperature is about 180°C (the melting point of the adhesive is about 163°C). The pressure is controlled so that the adhesive layer diffuses from the first main body area to the groove area of ​​the first tab area; and the mixture is cured at 70°C for 72 hours.

[0222] S5. Optionally, coating a protective adhesive layer (PMMA) on areas of the first and second aluminum foils that do not require thinning according to thickness requirements, and chemically thinning the surface of the second aluminum foil facing away from the adhesive layer; then removing the protective adhesive with acetone;

[0223] S6. Optionally, according to thickness requirements, a protective adhesive layer (PMMA) is coated on the areas of the first aluminum foil and the second aluminum foil that do not need to be thinned, the surface of the first aluminum foil facing away from the adhesive layer is etched, and then the protective adhesive is removed with acetone to obtain a composite current collector.

[0224] Current Collector Preparation Example 3:

[0225] S1. Take a first aluminum foil, apply a protective adhesive (PMMA) to the first tab area of ​​the first aluminum foil; etch the first main body area of ​​the first aluminum foil with a NaOH solution; and then remove the protective adhesive with acetone;

[0226] S2. Take a second aluminum foil, apply a protective adhesive (PMMA) to the second tab area of ​​the second aluminum foil; etch the second main body area of ​​the second aluminum foil with a NaOH solution; and then remove the protective adhesive with acetone;

[0227] S3. Prepare a bonding layer slurry, wherein the binder is maleic anhydride-modified polypropylene, the particulate material is metallic copper particles, and the conductive agent is carbon nanotubes. Dissolve 40% of the binder, 40% of the metallic copper particles, and 20% of the carbon nanotubes in an organic solvent in a mass ratio to prepare a bonding layer slurry with a solid content of 50%;

[0228] S4. Apply the above-mentioned adhesive layer slurry to the first main body area of ​​the first aluminum foil and dry it at 80°C to 100°C; hot-press the second aluminum foil on the surface of the adhesive facing away from the first aluminum foil, so that the first tab area of ​​the first aluminum foil and the second tab area of ​​the second aluminum foil extend toward each other. The hot-pressing temperature is about 180°C (the melting point of the adhesive is about 163°C). The pressure is controlled so that the adhesive layer diffuses from the first main body area to the first tab area and the second tab area; and the mixture is cured at 70°C for 72 hours.

[0229] S5. Optionally, coating a protective adhesive layer (PMMA) on areas of the first and second aluminum foils that do not require thinning according to thickness requirements, and chemically thinning the surface of the second aluminum foil facing away from the adhesive layer; then removing the protective adhesive with acetone;

[0230] S6. Optionally, according to thickness requirements, a protective adhesive layer (PMMA) is coated on the areas of the first aluminum foil and the second aluminum foil that do not need to be thinned, the surface of the first aluminum foil facing away from the adhesive layer is etched, and then the protective adhesive is removed with acetone to obtain a composite current collector.

[0231] Current Collector Preparation Example 4:

[0232] S1. Take a first aluminum foil, apply a protective adhesive (PMMA) to the first tab area of ​​the first aluminum foil; etch the first main body area of ​​the first aluminum foil with a NaOH solution; and then remove the protective adhesive with acetone;

[0233] S2, applying a protective glue (PMMA) to the non-groove area of ​​the first tab; etching the first main body area of ​​the first aluminum foil and the groove area of ​​the first tab with a NaOH solution; and then removing the protective glue with acetone;

[0234] S3, taking a second aluminum foil, applying a protective glue (PMMA) to the second tab area of ​​the second aluminum foil; etching the second main body area of ​​the second aluminum foil with a NaOH solution; and then removing the protective glue with acetone;

[0235] S4. Prepare a bonding layer slurry, wherein the binder is maleic anhydride-modified polypropylene, the particulate material is metallic copper particles, and the conductive agent is carbon nanotubes. Dissolve 40% of the binder, 40% of the metallic copper particles, and 20% of the carbon nanotubes in an organic solvent in a mass ratio to prepare a bonding layer slurry with a solid content of 50%;

[0236] S5. Apply the above-mentioned adhesive layer slurry to the first main body area of ​​the first aluminum foil and dry it at 80°C to 100°C; hot-press the second aluminum foil on the surface of the adhesive facing away from the first aluminum foil, so that the first tab area of ​​the first aluminum foil and the second tab area of ​​the second aluminum foil extend toward each other. The hot-pressing temperature is about 180°C (the melting point of the adhesive is about 163°C). The pressure is controlled so that the adhesive layer diffuses from the first main body area to the first tab area and the second tab area; and the mixture is cured at 70°C for 72 hours.

[0237] S6. Optionally, coating a protective adhesive layer (PMMA) on areas of the first and second aluminum foils that do not require thinning according to thickness requirements, and chemically thinning the surface of the second aluminum foil facing away from the adhesive layer; then removing the protective adhesive with acetone;

[0238] S7. Optionally, according to thickness requirements, a protective adhesive layer (PMMA) is coated on the areas of the first aluminum foil and the second aluminum foil that do not need to be thinned, the surface of the first aluminum foil facing away from the adhesive layer is etched, and then the protective adhesive is removed with acetone to obtain a composite current collector.

[0239] Current Collector Preparation Example 5:

[0240] S1. Take a first aluminum foil, apply a protective adhesive (PMMA) to the first tab area of ​​the first aluminum foil; etch the first main body area of ​​the first aluminum foil with a NaOH solution; and then remove the protective adhesive with acetone;

[0241] S2, applying a protective glue (PMMA) to the non-groove area of ​​the first tab; etching the first main body area of ​​the first aluminum foil and the groove area of ​​the first tab with a NaOH solution; and then removing the protective glue with acetone;

[0242] S3, taking a second aluminum foil, applying a protective glue (PMMA) to the second tab area of ​​the second aluminum foil; etching the second main body area of ​​the second aluminum foil with a NaOH solution; and then removing the protective glue with acetone;

[0243] S4, applying a protective sealant (PMMA) to the non-groove area of ​​the second tab; etching the second main body area of ​​the second aluminum foil and the groove area of ​​the second tab with a NaOH solution; and then removing the protective sealant with acetone;

[0244] S5. Prepare a bonding layer slurry, wherein the binder is maleic anhydride-modified polypropylene, the particulate material is metallic copper particles, and the conductive agent is carbon nanotubes. Dissolve 40% of the binder, 40% of the metallic copper particles, and 20% of the carbon nanotubes in an organic solvent in a mass ratio to prepare a bonding layer slurry with a solid content of 50%;

[0245] S6. Apply the above-mentioned adhesive layer slurry to the first main body area of ​​the first aluminum foil and dry it at 80°C to 100°C; hot-press the second aluminum foil on the surface of the adhesive facing away from the first aluminum foil, so that the first tab area of ​​the first aluminum foil and the second tab area of ​​the second aluminum foil extend toward each other. The hot-pressing temperature is about 180°C (the melting point of the adhesive is about 163°C). The pressure is controlled so that the adhesive layer diffuses from the first main body area to the first tab area and the second tab area; and the mixture is cured at 70°C for 72 hours.

[0246] S7. Optionally, coating a protective adhesive layer (PMMA) on areas of the first and second aluminum foils that do not require thinning according to thickness requirements, and chemically thinning the surface of the second aluminum foil facing away from the adhesive layer; then removing the protective adhesive with acetone;

[0247] S8. Optionally, according to thickness requirements, a protective adhesive layer (PMMA) is coated on the areas of the first aluminum foil and the second aluminum foil that do not need to be thinned, the surface of the first aluminum foil facing away from the adhesive layer is etched, and then the protective adhesive is removed with acetone to obtain a composite current collector.

[0248] Current Collector Preparation Example 6:

[0249] S1. Take a first aluminum foil, apply a protective adhesive (PMMA) to the first tab area of ​​the first aluminum foil; etch the first main body area of ​​the first aluminum foil with a NaOH solution; and then remove the protective adhesive with acetone;

[0250] S2, applying a protective glue (PMMA) to the non-groove area of ​​the first tab; etching the first main body area of ​​the first aluminum foil and the groove area of ​​the first tab with a NaOH solution; and then removing the protective glue with acetone;

[0251] S3. Prepare a bonding layer slurry, wherein the binder is maleic anhydride-modified polypropylene, the particulate material is metallic copper particles, and the conductive agent is carbon nanotubes. Dissolve 40% of the binder, 40% of the metallic copper particles, and 20% of the carbon nanotubes in an organic solvent in a mass ratio to prepare a bonding layer slurry with a solid content of 50%;

[0252] S4. Apply the above-mentioned adhesive layer slurry to the first main body area of ​​the first aluminum foil and dry it at 80° C. to 100° C.; then hot-press the second aluminum foil on the surface of the adhesive facing away from the first aluminum foil, with the first tab area of ​​the first aluminum foil extending toward the second tab area of ​​the second aluminum foil. The hot-pressing temperature is about 180° C. (the melting point of the adhesive is about 163° C.), and the pressure is controlled so that the adhesive layer diffuses from the first main body area to the first tab area.

[0253] S5. Hot pressing the first tab region of the first aluminum foil and the second tab region of the second aluminum foil again, so that the second adhesive layer melts and diffuses again and forms a thin adhesive layer in the non-groove region between the first tab region and the second tab region; curing at 70° C. for 72 hours;

[0254] S6. Optionally, coating a protective adhesive layer (PMMA) on areas of the first and second aluminum foils that do not require thinning according to thickness requirements, and chemically thinning the surface of the second aluminum foil facing away from the adhesive layer; then removing the protective adhesive with acetone;

[0255] S7. Optionally, according to thickness requirements, a protective adhesive layer (PMMA) is coated on the areas of the first aluminum foil and the second aluminum foil that do not need to be thinned, the surface of the first aluminum foil facing away from the adhesive layer is etched, and then the protective adhesive is removed with acetone to obtain a composite current collector.

[0256] Current Collector Preparation Example 7:

[0257] S1. Take a first aluminum foil, apply a protective adhesive (PMMA) to the first tab area of ​​the first aluminum foil; etch the first main body area of ​​the first aluminum foil with a NaOH solution; and then remove the protective adhesive with acetone;

[0258] S2, applying a protective glue (PMMA) to the non-groove area of ​​the first tab; etching the first main body area of ​​the first aluminum foil and the groove area of ​​the first tab with a NaOH solution; and then removing the protective glue with acetone;

[0259] S3, taking a second aluminum foil, applying a protective glue (PMMA) to the second tab area of ​​the second aluminum foil; etching the second main body area of ​​the second aluminum foil with a NaOH solution; and then removing the protective glue with acetone;

[0260] S4. Prepare a bonding layer slurry, wherein the binder is maleic anhydride-modified polypropylene, the particulate material is metallic copper particles, and the conductive agent is carbon nanotubes. Dissolve 40% of the binder, 40% of the metallic copper particles, and 20% of the carbon nanotubes in an organic solvent in a mass ratio to prepare a bonding layer slurry with a solid content of 50%;

[0261] S5. Coating the above-mentioned adhesive layer slurry to the first main body area of ​​the first aluminum foil and drying it at 80° C. to 100° C.; hot-pressing the second aluminum foil on the surface of the adhesive facing away from the first aluminum foil, with the first tab area of ​​the first aluminum foil and the second tab area of ​​the second aluminum foil extending toward each other, at a hot-pressing temperature of approximately 180° C. (the melting point of the adhesive is approximately 163° C.), and controlling the pressure so that the adhesive layer diffuses from the first main body area to the first tab area and the second tab area;

[0262] S6. Hot pressing the first tab region of the first aluminum foil and the second tab region of the second aluminum foil again, so that the second adhesive layer melts and diffuses again and forms a thin adhesive layer in the non-groove region between the first tab region and the second tab region; curing at 70° C. for 72 hours;

[0263] S7. Optionally, coating a protective adhesive layer (PMMA) on areas of the first and second aluminum foils that do not require thinning according to thickness requirements, and chemically thinning the surface of the second aluminum foil facing away from the adhesive layer; then removing the protective adhesive with acetone;

[0264] S8. Optionally, according to thickness requirements, a protective adhesive layer (PMMA) is coated on the areas of the first aluminum foil and the second aluminum foil that do not need to be thinned, the surface of the first aluminum foil facing away from the adhesive layer is etched, and then the protective adhesive is removed with acetone to obtain a composite current collector.

[0265] Current Collector Preparation Example 8:

[0266] S1. Take a first aluminum foil, apply a protective adhesive (PMMA) to the first tab area of ​​the first aluminum foil; etch the first main body area of ​​the first aluminum foil with a NaOH solution; and then remove the protective adhesive with acetone;

[0267] S2, applying a protective glue (PMMA) to the non-groove area of ​​the first tab; etching the first main body area of ​​the first aluminum foil and the groove area of ​​the first tab with a NaOH solution; and then removing the protective glue with acetone;

[0268] S3, taking a second aluminum foil, applying a protective glue (PMMA) to the second tab area of ​​the second aluminum foil; etching the second main body area of ​​the second aluminum foil with a NaOH solution; and then removing the protective glue with acetone;

[0269] S4, applying a protective sealant (PMMA) to the non-groove area of ​​the second tab; etching the second main body area of ​​the second aluminum foil and the groove area of ​​the second tab with a NaOH solution; and then removing the protective sealant with acetone;

[0270] S5. Prepare a bonding layer slurry, wherein the binder is maleic anhydride-modified polypropylene, the particulate material is metallic copper particles, and the conductive agent is carbon nanotubes. Dissolve 40% of the binder, 40% of the metallic copper particles, and 20% of the carbon nanotubes in an organic solvent in a mass ratio to prepare a bonding layer slurry with a solid content of 50%;

[0271] S6. Coating the above-mentioned adhesive layer slurry to the first main body area of ​​the first aluminum foil and drying it at 80° C. to 100° C.; hot-pressing the second aluminum foil on the surface of the adhesive facing away from the first aluminum foil, with the first tab area of ​​the first aluminum foil and the second tab area of ​​the second aluminum foil extending toward each other, at a hot-pressing temperature of approximately 180° C. (the melting point of the adhesive is approximately 163° C.), and controlling the pressure so that the adhesive layer diffuses from the first main body area to the first tab area and the second tab area;

[0272] S7, hot pressing the first tab region of the first aluminum foil and the second tab region of the second aluminum foil again, so that the second adhesive layer melts and diffuses again and forms a thin adhesive layer in the non-groove region between the first tab region and the second tab region; curing at 70° C. for 72 hours;

[0273] S8. Optionally, coating a protective adhesive layer (PMMA) on areas of the first and second aluminum foils that do not require thinning according to thickness requirements, and chemically thinning the surface of the second aluminum foil facing away from the adhesive layer; then removing the protective adhesive with acetone;

[0274] S9. Optionally, according to thickness requirements, a protective adhesive layer (PMMA) is coated on the areas of the first aluminum foil and the second aluminum foil that do not need to be thinned, the surface of the first aluminum foil facing away from the adhesive layer is etched, and then the protective adhesive is removed with acetone to obtain a composite current collector.

[0275] Current Collector Preparation Example 9:

[0276] S1. Take a first aluminum foil, apply a protective sealant (PMMA) to the first tab area on one surface of the first aluminum foil and the entire other surface, and etch the first main body area on the unprotected surface of the aluminum foil with a NaOH solution;

[0277] S2. Prepare a bonding layer slurry, wherein the binder is maleic anhydride-modified polypropylene, the particulate material is metallic copper particles, and the conductive agent is carbon nanotubes. 40% binder + 40% metal particles + 20% carbon nanotubes are dissolved in an organic solvent in a weight ratio to prepare a binder slurry with a solid content of 50%;

[0278] S3, coating the etched area of ​​the first aluminum foil with the adhesive slurry and drying it at 80° C. to 100° C.;

[0279] S4, evaporating an aluminum layer on the surface of the first tab region of the adhesive layer and the first aluminum foil; the first tab region extends toward the second tab region of the evaporated aluminum layer, and the second tab region is connected to the first tab region;

[0280] S5. Curing at 70° C. for 72 h to obtain a composite current collector.

[0281] Current Collector Preparation Example 10:

[0282] S1. Take a first aluminum foil, and coat the first tab region and the third tab region of the first aluminum foil with a protective adhesive (PMMA); etch the first main body region of the first aluminum foil with a NaOH solution; and then remove the protective adhesive with acetone;

[0283] S2. Prepare a bonding layer slurry, wherein the binder is maleic anhydride-modified polypropylene, the particulate material is metallic copper particles, and the conductive agent is carbon nanotubes. Dissolve 40% of the binder, 40% of the metallic copper particles, and 20% of the carbon nanotubes in an organic solvent in a mass ratio to prepare a bonding layer slurry with a solid content of 50%;

[0284] S3. Apply the above-mentioned adhesive layer slurry to the first main body area of ​​the first aluminum foil and dry it at 80°C to 100°C; hot-press the second aluminum foil on the surface of the adhesive facing away from the first aluminum foil, so that the first tab area and the third tab area of ​​the first aluminum foil extend toward the second tab area and the fourth tab area of ​​the second aluminum foil, respectively. The hot-pressing temperature is about 180°C (the melting point of the adhesive is about 163°C). The pressure is controlled so that the adhesive layer diffuses from the first main body area to the first tab area and the third tab area; and the mixture is cured at 70°C for 72 hours.

[0285] S4. Optionally, coating a protective adhesive layer (PMMA) on areas of the first and second aluminum foils that do not require thinning according to thickness requirements, and chemically thinning the surface of the second aluminum foil facing away from the adhesive layer; then removing the protective adhesive with acetone;

[0286] S5. Optionally, according to thickness requirements, a protective adhesive layer (PMMA) is coated on the areas of the first aluminum foil and the second aluminum foil that do not need to be thinned, the surface of the first aluminum foil facing away from the adhesive layer is etched, and then the protective adhesive is removed with acetone to obtain a composite current collector.

[0287] 2. Application Examples

[0288] Application Examples 1 to 3, 5:

[0289] The composite current collector was prepared by the method of current collector preparation Example 5. The composite current collector was assembled into a secondary battery through the steps of coating, cold pressing, die cutting, slitting, winding, hot pressing, welding, casing, formation, and sealing.

[0290] The DCR performance of the secondary battery, the temperature at the tab when the secondary battery is charged at 2C, the puncture performance and the energy density are tested.

[0291] The DCR performance test method is to adjust the battery to 50% SOC, discharge it at a rate of 4C (corresponding to a discharge current of I) for 30 seconds, and record the voltage difference ΔV before and after the 30-second discharge. The DCR corresponding to 50% SOC is calculated using the following formula: DCR = ΔV / I.

[0292] The testing method for the 2C charging tab temperature is: arrange the temperature sensing wire at the root of the tab and read its maximum temperature during the 2C high-rate charging process.

[0293] The needle penetration performance test method involves fully charging a battery cell and securing it to a fixture. The positive and negative poles of the battery cell are connected to voltage detection wires, and temperature-sensing wires are placed at multiple locations on the battery cell. A 3mm diameter, high-temperature-resistant steel needle is then inserted through the battery cell at a speed of 80mm / s. The cell is then left standing for one hour, and the voltage change over time is recorded. For this purpose, a battery that exhibits smoke, fire, or a voltage drop greater than 0.5V after one hour of penetration is considered a failure. A battery that exhibits no smoke or fire and a voltage drop of less than or equal to 0.5V after one hour of penetration is considered a pass.

[0294] The energy density test method is as follows: at room temperature, the manufactured secondary battery is charged for the first time with a current of 1C, the charging is constant current and constant voltage charging, the termination voltage is 4.2V, and the cut-off current is 0.05C; it is discharged with a current of 1C, the discharge termination voltage is 2.8V, and the discharge capacity Cb and discharge platform voltage U of the secondary battery during the first cycle are recorded.

[0295] Use a soft ruler or steel ruler with a minimum graduation of 1 mm to measure the length (L), width (W) and height (H) of the battery. The volume energy density of the secondary battery is calculated using the following formula:

[0296] Volume energy density = Cb*U / (L*W*H).

[0297] The structural parameters of the composite current collector and the performance test results of the secondary battery are shown in Table 1.

[0298] Application Example 4:

[0299] The composite current collector was prepared by the method of current collector preparation Example 3. The composite current collector was assembled into a secondary battery through the steps of coating, cold pressing, die cutting, slitting, winding, hot pressing, welding, casing, formation, and sealing.

[0300] The DCR performance of the secondary battery, the temperature at the tab when the secondary battery is charged at 2C, the needle puncture performance, and the energy density are tested. The testing method is the same as that of Application Example 1.

[0301] The structural parameters of the composite current collector and the performance test results of the secondary battery are shown in Table 1.

[0302] Application Examples 6-8, 10-16:

[0303] The composite current collector was prepared by the method of current collector preparation Example 8. The composite current collector was assembled into a secondary battery through the steps of coating, cold pressing, die cutting, slitting, winding, hot pressing, welding, casing, formation, and sealing.

[0304] The DCR performance of the secondary battery, the temperature at the tab when the secondary battery is charged at 2C, the needle puncture performance, and the energy density are tested. The testing method is the same as that of Application Example 1.

[0305] The structural parameters of the composite current collector and the performance test results of the secondary battery are shown in Table 1.

[0306] Application Example 9:

[0307] The composite current collector was prepared by the method of current collector preparation Example 6. The composite current collector was assembled into a secondary battery through the steps of coating, cold pressing, die cutting, slitting, winding, hot pressing, welding, casing, formation, and sealing.

[0308] The DCR performance of the secondary battery, the temperature at the tab when the secondary battery is charged at 2C, the needle puncture performance, and the energy density are tested. The testing method is the same as that of Application Example 1.

[0309] The structural parameters of the composite current collector and the performance test results of the secondary battery are shown in Table 1.

[0310] Application Examples 17 to 21:

[0311] The composite current collector was prepared by the method of current collector preparation example 1. The composite current collector was assembled into a secondary battery through the steps of coating, cold pressing, die cutting, slitting, winding, hot pressing, welding, casing, formation, and sealing.

[0312] The DCR performance of the secondary battery, the temperature at the tab when the secondary battery is charged at 2C, the needle puncture performance, and the energy density are tested. The testing method is the same as that of Application Example 1.

[0313] The structural parameters of the composite current collector and the performance test results of the secondary battery are shown in Table 1.

[0314] Application Examples 22-23:

[0315] A composite current collector prepared using the same method as in Example 6, except that the thickness of the second adhesive layer and the thickness of the non-grooved region of the second adhesive layer were different, was assembled into a secondary battery through the following steps: coating, cold pressing, die-cutting, slitting, winding, hot pressing, welding, casing, formation, and sealing.

[0316] The DCR performance of the secondary battery, the temperature at the tab when the secondary battery is charged at 2C, the needle puncture performance, and the energy density are tested. The testing method is the same as that of Application Example 1.

[0317] The structural parameters of the composite current collector and the performance test results of the secondary battery are shown in Table 1.

[0318] Application Examples 24 to 29:

[0319] A composite current collector prepared using the same method as in Example 1, except that the thicknesses of the first main body region, the second main body region, the first tab region, and the second tab region were different, was assembled into a secondary battery through coating, cold pressing, die-cutting, slitting, winding, hot pressing, welding, casing, formation, and sealing.

[0320] The DCR performance of the secondary battery, the temperature at the tab when the secondary battery is charged at 2C, the needle puncture performance, and the energy density are tested. The testing method is the same as that of Application Example 1.

[0321] The structural parameters of the composite current collector and the performance test results of the secondary battery are shown in Table 1.

[0322] Application Examples 30-32:

[0323] The composite current collector was prepared by the method of current collector preparation Example 9. The composite current collector was assembled into a secondary battery through the steps of coating, cold pressing, die cutting, slitting, winding, hot pressing, welding, casing, formation, and sealing.

[0324] The DCR performance of the secondary battery, the temperature at the tab when the secondary battery is charged at 2C, the needle puncture performance, and the energy density are tested. The testing method is the same as that of Application Example 1.

[0325] The structural parameters of the composite current collector and the performance test results of the secondary battery are shown in Table 2.

[0326] 3. Application comparison

[0327] Application Comparative Example 1:

[0328] A pure aluminum foil metal current collector with a thickness of 13 μm is used. The current collector is assembled into a secondary battery through the processes of coating, cold pressing, die cutting, slitting, winding, hot pressing, welding, shelling, formation, and sealing.

[0329] The DCR performance of the secondary battery, the temperature at the tab when the secondary battery is charged at 2C, the needle puncture performance, and the energy density are tested. The testing method is the same as that of Application Example 1.

[0330] The structural parameters of the composite current collector and the performance test results of the secondary battery are shown in Table 2.

[0331] In the following Tables 1 and 2, the groove depths of the first tab region and the second tab region are A1 and A2 respectively, and the groove widths are both W1; the width of the second adhesive layer is W1 and the thickness is D1, and the groove and the second adhesive layer have the same width; the width of the second adhesive layer excluding the groove is W11, and the thickness of the second adhesive layer outside the groove is D11; the width of the first tab region is W2 (W2=50mm), the thickness of the first tab region is D3, and the thickness of the second tab region is D4; the thickness of the first main body region is D21, and the thickness of the second main body region is D22.

[0332] Table 1

[0333] From the above application examples, we can know that:

[0334] In application examples 1 to 5, when the ratio of W1 / W2 is controlled in the range of 5% to 50% (the width of W1 is controlled in the range of 2.5mm to 25mm), the second adhesive layer can not only play the role of supporting the tab, but also use the metal layer in the area without the adhesive layer as the main welding site, which not only prevents the root of the tab from being damaged during the processing, but also obtains good welding effect and conductive performance, thereby reducing the DCR of the battery cell, and the tab temperature of the battery cell charged at a high rate of 2C is within the normal range, thereby improving the performance and safety of the battery cell.

[0335] In Example 3, grooves are present in both the first and second tab regions, while in Example 4, grooves are not present in both the first and second tab regions. The bonding layers in the second regions can both support the base of the tabs, and thus better cell performance can be achieved. Compared with Example 3, in Example 4, since grooves are not present in both the first and second tab regions, in order to connect the first bonding layer and the second bonding layer, the thickness of the first bonding layer in Example 4 is set thicker, and thus the energy density is partially lost compared to Example 3.

[0336] In application examples 6 to 7, the second adhesive layer has a thin adhesive layer (0.3 μm) outside the groove. When its width W11 is 25 mm or 45 mm, it represents partial and full coverage of the non-groove area respectively, making the metal layer in the tab area less likely to be damaged during processing, ensuring better DCR and high-rate charging tab temperature rise performance.

[0337] In application example 20, when W1 and W1 / W2 are 0, the root of the tab lacks support, which causes cracks to form easily at the root of the tab during processing, ultimately leading to a decrease in the tab's conductivity and the performance of the battery cell.

[0338] In application example 21, when W1 / W2 exceeds 50% and reaches 70%, the metal layer in the area without the bonding layer is too small, resulting in a reduction in the area of ​​the metal area that can be directly welded. Most of the welding process needs to be done in the area containing the bonding layer, which affects the welding effect and the conductivity during welding, resulting in an increase in the DCR of the battery cell, a decrease in the overcurrent capacity of the battery cell, and an increase in the temperature of the 2C charging tab.

[0339] In application examples 8 to 14, the thickness of the second adhesive layer in the groove is controlled at 0.5μm to 5μm. When the ratio of the sum of the thickness of the first tab area and the second tab area to the thickness of the second adhesive layer in the groove is 2 to 20, the tab welding effect is good and the cell DCR is normal. However, in application example 22, when the thickness of the second adhesive layer in the groove exceeds 5μm and the ratio of the sum of the thickness of the first tab area and the second tab area to the thickness of the second adhesive layer in the groove is 1.25, the metal layer at the root of the first tab area and the second tab is relatively thin, and the adhesive layer is too thick, resulting in the adhesive layer being unable to be penetrated by ultrasonic energy during welding, the conductivity of the upper and lower metal layers at this location becomes weak, and the overall conductivity decreases. Therefore, controlling the thickness D1 of the second adhesive layer in the groove to 0.5μm to 5μm and (D3+D4) / D1 to between 2 and 20 can ensure a better welding effect.

[0340] In Example 9, the first tab region extends toward the second tab region, and in Example 8, the first tab region extends toward the second tab region while the second tab region also extends toward the first tab region. Both Example 9 and Example 8 can achieve good battery cell performance, indicating that both tab extension methods are desirable.

[0341] In Example 8, both the first tab region and the second tab region contain groove regions, and in Example 9, only the first tab region contains a groove region. Both cases can achieve better battery cell performance, indicating that the arrangement of the groove regions can be diversified.

[0342] Comparing Application Examples 15 to 16 with Application Example 23, when the thickness of the area outside the groove of the second bonding layer is ≤0.5μm, it plays a role in reinforcing the first tab area and the second tab area, so that the processability becomes stronger, and the very thin bonding layer does not affect direct welding; however, when the thickness of the area outside the groove of the second bonding layer reaches >0.5μm, for example, reaching 1μm (Application Example 23), it affects the conduction of the upper and lower metal layers, and affects the conductive performance of the directly welded tabs, thereby increasing the DCR, charging at a high rate of 2C, and increasing the temperature at the tabs, affecting the performance of the battery cell.

[0343] In application examples 17 to 19, the total thickness of the first tab area and the second tab area is 7μm to 15μm, and the difference between the total thickness of the first tab area and the second tab area and the total thickness of the first main body area and the second main body area (D3+D4)-(D21+D22) is between 5μm and 13μm, which can achieve better results, the DCR of the battery cell is low, and the tab temperature rise is also at a normal level; at this time, if the D3+D4 thickness is increased, there is no significant improvement in the DCR and fast charging temperature rise, and the energy density is greatly deteriorated (in application example 24, D3+D4 is 26μm). Therefore, considering the comprehensive energy density and battery cell performance, it is better to control the total thickness of the first tab area and the second tab area to 7μm to 15μm, and (D3+D4)-(D21+D22) between 5μm and 13μm can take into account both the tab conductivity and the battery cell energy density.

[0344] In application example 25, the total thickness of D3+D4 is 5μm. Although it is 3μm thicker than (D21+D22), the conductivity of the tab area is insufficient, resulting in an increase in the DCR of the battery cell. The tab temperature rises high during 2C charging, and there is a risk of battery cell failure.

[0345] In Application Examples 26-29, when the total thickness (D21+D22) of the first and second main body regions was 4μm-10μm, the electrode metal layer was too thick and failed the needle penetration test. This further illustrates that the electrode metal layer should not be too thick. Controlling the electrode and tab metal layers within an appropriate range helps improve both cell safety and energy density.

[0346] Table 2

[0347] It can be seen from Table 2 that in application examples 30 to 32, the first main body area and the first tab area are made of metal foil, and the second main body area and the second tab area are directly prepared by metal evaporation, so that the connectivity of the metal in the first tab area and the second tab area is better, the conductivity of the upper and lower metal layers is better, and the conduction area of ​​the first tab area and the second tab area is larger, thereby obtaining good DCR performance and suppressing fast charging temperature rise. Good battery cell DCR performance can be obtained when the thickness of the metal layer in the second main body area is between 0.5μm and 1μm, and the 2C charging temperature rise is also within the normal range, reaching a level comparable to that of aluminum foil (application comparison example 1), and while ensuring performance, it can also directly pass the puncture test to improve battery cell safety. The aluminum foil group cannot pass the puncture test (application comparison example 1). It proves the role of the current collector used in application examples 30 to 32 of this application in improving battery cell performance and safety.

[0348] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A composite current collector, comprising a first metal layer, a second metal layer and a first bonding layer, wherein the first metal layer comprises a first main body region and a first pole lug region, the first pole lug region is located at an end of the first metal layer, the second metal layer comprises a second main body region and a second pole lug region, the second pole lug region is located at an end of the second metal layer, the first main body region and the second main body region are connected through the first bonding layer, the thickness of the first pole lug region is greater than the thickness of the first main body region, and the first pole lug region extends toward the second pole lug region.

2. The composite current collector according to claim 1, It is characterized in that A first groove is disposed at one end of the first pole lug region extending toward the second pole lug region, and the first groove extends from one side of the first pole lug region close to the first main body region to the other side.

3. The composite current collector according to claim 2, It is characterized in that The thickness of the second tab region is greater than the thickness of the second body region, and the second tab region extends toward the first tab region.

4. The composite current collector according to claim 3, It is characterized in that A second groove is disposed at one end of the second pole lug region extending toward the first pole lug region, and the second groove extends from one side of the second pole lug region close to the second main body region to the other side.

5. The composite current collector according to claim 4, It is characterized in that A second bonding layer is provided between the first pole tab region and the second pole tab region, and the second bonding layer at least partially fills a gap between the first pole tab region and the second pole tab region.

6. The composite current collector according to claim 5, It is characterized in that The thickness of the second bonding layer at the first groove and / or the second groove is 0.5 μm to 5 μm, and the thickness of other parts of the second bonding layer is less than 0.5 μm; Optionally, the thickness of the second adhesive layer at the first groove and / or the second groove is 0.5 μm to 3 μm.

7. The composite current collector according to claim 5 or 6, It is characterized in that The ratio of the total thickness of the first tab region and the second tab region to the thickness of the second bonding layer at the first groove and / or the second groove is greater than or equal to 2; Optionally, the ratio of the total thickness of the first tab region and the second tab region to the thickness of the second bonding layer at the first groove and / or the second groove is 2-20.

8. The composite current collector according to any one of claims 5 to 7, It is characterized in that The composite current collector satisfies at least one of the following (1) to (4): (1) The ratio of the width of the first groove to the width of the first tab region is 0.05 to 0.5; (2) The ratio of the width of the second bonding layer in the first groove to the width of the first tab region is 0.05 to 0.5; (3) The ratio of the width of the second groove to the width of the second tab region is 0.05 to 0.5; (4) The ratio of the width of the second adhesive layer in the second groove to the width of the second tab region is 0.05 to 0.

5.

9. The composite current collector according to any one of claims 5 to 8, It is characterized in that The composite current collector satisfies at least one of the following (5) to (8): (5) A side of the second tab region close to the second main body region is in contact with the first bonding layer; (6) The first tab region is connected to the second tab region; (7) the second adhesive layer is connected to the first adhesive layer; (8) A side of the first tab region close to the first main body region is in contact with the first adhesive layer.

10. The composite current collector according to any one of claims 1 to 9, It is characterized in that The first metal layer includes a plurality of the first main body regions, which are separated from each other by a third pole lug region; the second metal layer includes a plurality of the second main body regions, which are separated from each other by a fourth pole lug region; the thickness of the third pole lug region is greater than that of the first main body region, and the third pole lug region extends toward the fourth pole lug region.

11. The composite current collector according to claim 10, It is characterized in that The composite current collector satisfies at least one of the following (9) to (11): (9) The thickness of the fourth tab region is greater than the thickness of the second main body region, and the fourth tab region extends toward the third tab region; (10) The side wall of the fourth electrode tab region is in contact with the first bonding layer; (11) The third electrode tab region is connected to the fourth electrode tab region.

12. The composite current collector according to claim 10 or 11, It is characterized in that The composite current collector satisfies at least one of the following (12) to (14): (12) a third bonding layer is provided between the third pole tab region and the fourth pole tab region, and the third bonding layer at least partially fills the gap between the third pole tab region and the fourth pole tab region; (13) the third adhesive layer is connected to the first adhesive layer; (14) The side wall of the third electrode tab region is in contact with the first adhesive layer.

13. The composite current collector according to claim 12, It is characterized in that The thickness of the third bonding layer is 0.5 μm to 5 μm; Optionally, the thickness of the third adhesive layer is 0.5 μm to 3 μm.

14. The composite current collector according to any one of claims 1 to 13, It is characterized in that The sum of the thickness of the first tab region and the thickness of the second tab region is greater than or equal to 7 μm; Optionally, the sum of the thickness of the first tab region and the thickness of the second tab region is 7 μm to 15 μm.

15. The composite current collector according to any one of claims 10 to 13, It is characterized in that The sum of the thickness of the third tab region and the thickness of the fourth tab region is greater than or equal to 7 μm; Optionally, the sum of the thickness of the third tab region and the thickness of the fourth tab region is 7 μm to 15 μm.

16. The composite current collector according to any one of claims 1 to 15, It is characterized in that The sum of the thicknesses of the first tab region and the second tab region is 5 μm to 13 μm greater than the sum of the thicknesses of the first body region and the second body region.

17. The composite current collector according to any one of claims 10 to 13 and 15, It is characterized in that The sum of the thicknesses of the third tab region and the fourth tab region is 5 μm to 13 μm greater than the sum of the thicknesses of the first body region and the second body region.

18. The composite current collector according to any one of claims 1 to 17, It is characterized in that The first bonding layer contains a bonding agent and one or more of a particulate material and a conductive agent.

19. The composite current collector according to claim 18, It is characterized in that The composite current collector satisfies at least one of the following (15) to (18): (15) The particulate material includes one or more of inorganic compound particles and metal particles; (16) The conductive agent includes one or more of carbon nanotubes, conductive carbon, graphene, and conductive polymers; (17) The sum of the mass proportions of the particulate material and the conductive agent in the first bonding layer is 20% to 70%; (18) The binder includes one or more of polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polyethylene grafted with carboxylic acid and its derivatives, polypropylene, polypropylene grafted with carboxylic acid and its derivatives, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polymethyl methacrylate, polyethylene glycol, polysulfur nitride, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, polypyrrole, polythiophene, polyaniline, and phenolic resin.

20. A secondary battery, It is characterized in that A composite current collector comprising any one of claims 1 to 19.

21. An electrical device, It is characterized in that Includes the secondary battery as claimed in claim 20.